Study of ultrasound-guided percutaneous microwave ablation combined with portal vein embolization for rapid future liver remnant increase of planned hepatectomy - Hu, Qiaohong; Zeng, Zeng; Zhang, Yuanbiao; Fan, Xiaoming (Frontiers in Oncology, 2023)
Purpose To evaluate the efficacy of ultrasound-guided percutaneous microwave ablation (PMA) combined with portal vein embolization (PVE) for planned hepatectomy. Methods We retrospectively reviewed data of 18 patients with multiple right liver tumors or hilar tumor of liver invades the surrounding tissue and insufficient future liver remnant (FLR) for hepatectomy from July 2015 to March 2017. Ultrasound-guided PMA was performed by using PMCT cold circulation microwave treatment apparatus. PVE was performed after PMA. The increase of FLR was evaluated by computed tomography (CT) 6-22 days after PVE. The proportion of FLR, increase in the amplitude of FLR, procedure-related complications, perioperative morbidity and mortality, and overall survival (OS) rates, the median survival time were analyzed. Results The median volume of FLR before PMA and PVE was 369.7 ml (range: 239.4-493.1 ml). After a median waiting period of 11.5 days (range: 6-22 days), the median volume of FLR was increased to 523.4 ml (range: 355.4-833.3 ml). The changes in FLR before and after PMA and PVE were statistically significant (p<0.001). No serious perioperative complications or mortality were found. After a median follow-up time of 51.0 months (range: 2-54 months), the 6-month, 1-year, 2-year, 3-year and 4-year survival rates were 88.9%, 72.2%, 44.4%, 33.3%, 22.2%, respectively, and the median survival time was 15.0 ± 7.1 months. Conclusion PMA combined with PVE increases FLR rapidly, avoids touching malignant tumors, and produces fewer procedure-related complications. It appears safe and efficacious for planned hepatectomy.